Adult mice with noise-induced hearing loss exhibited temporal ordering memory deficits accompanied by microglia-associated neuroplastic changes in the medial prefrontal cortex - Qian Li; Xiaomin Kang; Linchen Liu; Yu Xiao; Dan Xu; Hong Zhuang; Haiqing Liu; Jingyi Zhao; Han Zou; Jianing Yang; Xindi Zhan; Tianxiao Li; et al. (Neurobiology of Disease, 2023)
Acquired peripheral hearing loss in midlife is considered the primary modifiable risk factor for dementia, while the underlying pathological mechanism remains poorly understood. Excessive noise exposure is the most common cause of acquired peripheral hearing loss in modern society. This study was designed to investigate the impact of noise-induced hearing loss (NIHL) on cognition, with a focus on the medial prefrontal cortex (mPFC), a brain region that is involved in both auditory and cognitive processes and is highly affected in patients with cognitive impairment. Adult C57BL/6 J mice were randomly assigned to a control group and seven noise groups: 0HPN, 12HPN, 1DPN, 3DPN, 7DPN, 14DPN, and 28DPN, which were exposed to broadband noise at a 123 dB sound pressure level (SPL) for 2 h and sacrificed immediately (0 h), 12 h, or 1, 3, 7, 14, or 28 days post-noise exposure (HPN, DPN), respectively. Hearing assessment, behavioral tests, and neuromorphological studies in the mPFC were performed in control and 28DPN mice. All experimental animals were included in the time-course analysis of serum corticosterone (CORT) levels and mPFC microglial morphology. The results illustrated that noise exposure induced early-onset transient serum CORT elevation and permanent moderate-to-severe hearing loss in mice. 28DPN mice, in which permanent NIHL has been verified, exhibited impaired performance in temporal order object recognition tasks concomitant with reduced structural complexity of mPFC pyramidal neurons. The time-course immunohistochemical analysis in the mPFC revealed significantly higher morphological microglial activation at 14 and 28 DPN, preceded by a remarkably higher amount of microglial engulfed postsynaptic marker PSD95 at 7 DPN. Additionally, lipid accumulation in microglia was observed in 7DPN, 14DPN and 28DPN mice, suggesting a driving role of lipid handling deficits following excessive phagocytosis of synaptic elements in delayed and sustained microglial abnormalities. These findings provide fundamentally novel information concerning mPFC-related cognitive impairment in mice with NIHL and empirical evidence suggesting the involvement of microglial malfunction in the mPFC neurodegenerative consequences of NIHL.